Geoprocessamento dos casos de acidente vascular cerebral em Sobral - Ceará. - Arruda, Ana Karoline Soares (2021)
Cerebrovascular accident (CVA) is the second most common cause of death and the third cause in resources worldwide, however the distribution of these events is clearly hetero- geneous, being more prevalent in countries low and middle income. In addition, different studies have shown that social determinants, such as education, occupation, income, gen- der and ethnicity, are associated with the prevalence of stroke, and its risk factors, aggra- vating the disease burden in vulnerable populations. Therefore, it is necessary to measure these differences in order to subsidize public policies that reduce health inequalities. The- refore, geoprocessing is a valuable tool for the prevention, identification, monitoring, sur- veillance and control of stroke. Given the above, it is intended to analyze the spatial dis- tribution of the Stroke in Sobral - Ceará, using geoprocessing techniques. This study re- presents an excerpt from the Brazilian Epidemiological Registry and Biobank of Brazilian Cerebrovascular Accident survey. This is an ecological, cross-sectional study with a quantitative approach, carried out in the municipality of Sobral, composed of 260 sub- jects, from which the variables of interest were selected. The treatment of the data follo- wed the following steps: Descriptive Statistical Analysis, for which the Ex-cel 2010 sof- tware, Mapping and Spatial Analysis was used, with the support of the Quantum GIS 2.14.18 and GeoDa version 1.12 software. The research was submitted to the Research Ethics Committee involving human beings, being approved with the opinion number 828,538. As for the results found, the profile of people affected by stroke in the city cor- responds to the majority of males (53.46%), elderly people over 60 years old (71.90%), browns (57.69%), illiterate or with low education (74.61%), 86.14% with receive up to a minimum wage, approximately one fifth of the affected people stated that they have a parent or a first-degree relative who suffered a stroke, the most subtype frequent disease was ischemic (78.84%), the most prevalent modifiable factors being systemic arterial hypertension, dyslipidemia, diabetes mellitus and sedentary lifestyle. When proceeding to the exploratory analysis of spatial data, it appears that the neighborhoods that have spatial dependence for stroke cases in Sobral, in their majority, are located more on the periphery, in regions that house the smallest portion of community equipment. These re- sults corroborate with the literature when they point out that social inequalities have an important role in the illness of stroke, in view of the commitment of the population, es- pecially the most needy, to access to health care, from the level of promotion, prevention and appropriate treatment of diseases. The Family Health Strategy, thus, emerges as aneconomic strategy to face the growing burden of diseases, being associated with the re- duction of morbidity and mortality through the development of actions to promote, pre- vent and monitor modifiable risk factors for stroke.